The Effect of Harbolnas Discounts and Free Shipping on the Purchase Decision of Digital Business Study Program Students With Purchase Interest as an Intervening Variable - Farhan Fajar Sidiq; Osly Usman; Muhamad Vicky Abdillah, (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
The purpose of this study is to examine how Harbolnas discounts (X1) and free shipping (X2) affect the purchase decision (Y) of students enrolled in the Digital Business study program of the State University of Jakarta, with Purchase interest as an intervening variable (Z). Data for this study is gathered using a quantitative methodology based on surveys an online Google Form questionnaire. The research respondents consisted of one hundred active students who also used Shopee. Prior to the analysis utilizing Smart Partial Least Square 4.0 (SPLS), the study instrument underwent validity and reliability testing. The results of the analysis show that the X1 harbolnas discount and free shipping X2 have an effect on consumer purchase decisions. However, the intervening variable in the form of Purchase interest did not affect the purchase decision. These results provide a strategic view for e-commerce to prioritize discount-based promotions during the Harbolnas program to attract consumers more effectively